2018
DOI: 10.1638/2017-0191.1
|View full text |Cite
|
Sign up to set email alerts
|

NEW APPROACH TO STRESS RESEARCH IN PHOCIDS—POTENTIAL OF DEHYDROEPIANDROSTERONE AND CORTISOL/DEHYDROEPIANDROSTERONE RATIO AS MARKERS FOR STRESS IN HARBOR SEALS (PHOCA VITULINA) AND GRAY SEALS (HALICHOERUS GRYPUS)

Abstract: Cortisol is known to reflect the level of the stress response. However, measuring the cortisol concentration only once fails to provide sufficient information about the duration of the stress exposure. Moreover, handling is an acute stressor and increases cortisol secretion especially in wildlife species. Yet, in phocids reliable indicators are missing that reflect potential chronic effects of stress. The adrenal-derived steroid hormone dehydroepiandrosterone (DHEA) has been described as biomarker for the asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Although observed in other species, the potential role of DHEA as stress marker is not yet well understood in marine mammals ( O'Brien et al . 2017 ; Gundlach et al . 2018 ; McCormley et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although observed in other species, the potential role of DHEA as stress marker is not yet well understood in marine mammals ( O'Brien et al . 2017 ; Gundlach et al . 2018 ; McCormley et al .…”
Section: Discussionmentioning
confidence: 99%
“…This highlights that the gonads are the major source of DHEA in the giant panda, in-keeping with species such as rats (Belanger et al 1989;Belanger et al 1990;van Weeren et al 1992), guinea pigs (Rivarola et al 1968Belanger et al 1989), rabbits (Cutler et al 1978;Schiebinger et al 1981), dogs (Cutler et al 1978;Schiebinger et al 1981;Mongillo et al 2014) and cattle (Marinelli et al 2007). This is in contrast to species such as humans (Labrie et al 2005), primates (western lowland gorillas (Edes, 2017)), chimpanzees (Seraphin et al 2008;Blevins et al 2013), bonobos (Behringer et al 2012), macaques (Muehlenbein et al 2002), red squirrels (Boonstra et al 2008), American martens (Boonstra et al 2018) and both Gray and Harbor seals (Gundlach et al 2018) which have a primarily adrenal source for DHEA. Other Ursid species have not had the source of their DHEA investigated.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, Almeida and colleagues [ 20 ] suggested that the cortisol:DHEA ratio may serve as a biomarker of inflammatory foot lesions. Similarly, in a study of seals (harbor and gray), wild seals suffering from disease had lower serum DHEA concentrations and higher cortisol:DHEA ratios than both healthy wild seals and zoo-living seals [ 24 ]. Because serum cortisol did not differ between the wild healthy seals and wild diseased seals, the authors suggest that the cortisol:DHEA ratio may better reflect the functionality of the HPA axis.…”
Section: Glucocorticoid:dhea Ratiomentioning
confidence: 99%
“…In this review article, we provide an overview of the HPA axis, describe the primary actions of glucocorticoids and DHEA(S), discuss the pathophysiological effects of HPA dysfunction, and consider how the ratio of glucocorticoids to DHEA(S) may be applied to animal welfare research. However, we should note that while the cortisol:DHEA(S) ratio has been employed in studies of human development, psychology and immunology, there has been relatively little research on how this ratio may provide insight into the physical, mental and emotional health of non-human animals [ 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Therefore, we will explore the benefits of integrating this biomarker into animal welfare monitoring schemes and discuss potential methods for applying this metric in managed care settings.…”
Section: Introductionmentioning
confidence: 99%